Deformability and size-based cancer cell separation using an integrated microfluidic device. Issue 21 (14th September 2015) - Pang, Long; Shen, Shaofei; Ma, Chao; Ma, Tongtong; Zhang, Rui; Tian, Chang; Zhao, Lei; Liu, Wenming; Wang, Jinyi
Abstract : We present an integrated microfluidic device for cell separation based on the cell size and deformability by combining the microstructure-constricted filtration and pneumatic microvalves. Abstract : Cell sorting by filtration techniques offers a label-free approach for cell separation on the basis of size and deformability. However, filtration is always limited by the unpredictable variation of the filter hydrodynamic resistance due to cell accumulation and clogging in the microstructures. In this study, we present a new integrated microfluidic device for cell separation based on the cell size and deformability by combining the microstructure-constricted filtration and pneumatic microvalves. Using this device, the cell populations sorted by the microstructures can be easily released in real time for subsequent analysis. Moreover, the periodical sort and release of cells greatly avoided cell accumulation and clogging and improved the selectivity. Separation of cancer cells (MCF-7, MDA-MB-231 and MDA231-LM2) with different deformability showed that the mixture of the less flexible cells (MCF-7) and the flexible cells (MDA-MB-231 and MDA231-LM2) can be well separated with more than 75% purity. Moreover, the device can be used to separate cancer cells from the blood samples with more than 90% cell recovery and more than 80% purity. Compared with the current filtration methods, the device provides a new approach for cancer cell separation with high collection recovery and purity, and also, possesses practical potential to be applied as a sample preparation platform for fundamental studies and clinical applications.